Noradrenaline and Post-Traumatic Stress Disorder - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2016)
Noradrenaline (NA), a well known catecholamine has become the key transmitter involved in the generation of the autonomic symptoms present in the post-traumatic stress disorder (PTSD). It is present in the specialized noradrenergic pathways and in the cell nuclei located in the central nervous system that are involved in the pathophysiology of the disease. The locus coeruleus (LC) in the rostral pons is a region that has high NA content and it forms the center of the neurochemical traffic of PTSD. Experiments in rats have shown that NA content is increased in the LC in cat litter tests. NA levels in the cerebrospinal fluid increase in response to psychological stressors. The hippocampus receives NA only from the LC and the LC also sends efferents to the neocortex and the amygdala. The beta adrenergic receptors located in the lateral amygdala have been shown to be involved in fear conditioning. Projections arising from the LC also innervate the paraventricular nucleus of the hypothalamus, an important structure acting as a sympathetic premotor nucleus, a central controller of autonomic functions. The LC also receives reciprocal projections from these regions. Human data have also revealed that people with high catecholamine levels are more prone to develop PTSD. It may be accepted that excessive adrenergic activation following a traumatic event may enhance the memory consolidation of the event and increase the frequency of re-experiencing the event upon confronting a reminder. The activity of NA present in synapses is terminated by NA transporters ( NET). Polymorphisms in enzymes like catechol-O-methyl transferase which is responsible for the cleavage of NA and in the human NET may also play important roles in the development and maintenance of the disease. Various agents affecting noradrenergic receptors may further become therapeutic tools. Yohimbine, an alpha(2) adrenergic receptor antagonist can induce flashbacks and as the distribution of adrenergic alpha(2c) receptor is restricted to the CNS, this subtype has been the subject of many investigations of psychiatric diseases including PTSD. As alpha(2) receptors are presynaptic receptors and control the release of NA, inhibition of these presynaptic receptors may also cause an increase in NA synaptic levels. Clinical trials to date have shown promising results for prazosin, an alpha(1) adrenergic receptor blocker. Unfortunately, the trials performed with guanfacine, an alpha(2) adrenergic receptor agonist, were not effective in PTSD. Propranolol, a nonselective beta adrenergic receptor antagonist may help to prevent the disease if administered early following the trauma.
Keywords: CORTICOTROPIN-RELEASING-FACTOR; LOCUS-CERULEUS NEURONS; SINGLE-UNIT RESPONSE; FREELY MOVING CATS; NEUROPEPTIDE-Y NPY; BASOLATERAL AMYGDALA; NORADRENERGIC MODULATION; PRESENTED STRESSFUL; COMBAT VETERANS; PRAZOSIN